The Intersectionality of Sex and Race in the Relationship Between Posttraumatic Stress Disorder and Cardiovascular Disease: A Scoping Review - Lauren D. Hunter; Tara Boer; Leia Y. Saltzman (Frontiers Media S.A., 2023)
Objectives: Posttraumatic stress disorder (PTSD) has been linked with cardiovascular disease (CVD), suggesting a risk for negative health outcomes among individuals with PTSD. This review synthesizes the temporal relationship between PTSD and CVD and highlights the intersection of sex and race.Methods: Covidence was used to systematically review the literature published between 1980 and 2020.Results: 176 studies were extracted. 68 (38.64%) of the studies were a predominantly male sample. 31 studies (17.61%) were a predominantly female sample. Most reported participants of both sexes (n = 72; 40.91%) and only 5 (2.84%) did not report respondent sex. No studies reported transgender participants. 110 (62.5%) studies reported racial and ethnic diversity in their study population, 18 (10.22%) described a completely or predominantly white sample, and 48 (27.27%) did not report race or ethnicity of their study population.Conclusion: A compelling number of studies did not identify sex differences in the link between PTSD and CVD or failed to report race and ethnicity. Investigating sex, race, ethnicity, and the temporal relationship between PTSD and CVD are promising avenues for future research.